Neonatal Biliary Obstruction Caused by Pancreatic Kaposi Hemangioendothelioma - Magd Ahmed Kotb; Sherif Kaddah; Sally TM El Sorogy; Reham Osama; Naglaa El Kinaaiee; Sayed Khedr; Mostafa Gad (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Kaposiform hemangioendothelioma (KHE), is a rare benign locally invasive proliferation of blood vessels that forms a mass. Besides the mass effect of KHE, it infiltrates adjacent tissues, it can be associated with severe thrombocytopenia, consumptive coagulopathy with high mortality rate. The manifestations of KHE are variable and range from cutaneous lesions with wide varieties of appearances to deep masses without cutaneous signs. We report a case of 3 month old male who presented as extrahepatic biliary atresia in the form of jaundice, hepatomegaly, clay colored stool and elevated liver enzymes. Dynamic Magnetic Resonance Imaging revealed pancreatic head solid mass. Operative findings and biopsy of the highly vascular lesion confirmed that it was KHE of head of pancreas. The mass was excised and hepato-portoenterostomy was successfully performed. One year later the boy is disease free with no organomegaly or any other complication. KHE of head of pancreas is a very rare cause of extrahepatic biliary obstruction early in life. It is amenable to successful surgical intervention.